Despite large choice of effective therapies: Individuals with psoriasis still seem undertreated. (6th May 2021) - Pilz, Anna Caroline; Zink, Alexander; Schielein, Maximilian C.; Hell, Katharina; Romer, Katrin; Hillmann, Elena; Bäumer, Daniel; Reinhardt, Maximilian; Wagner, Nicola
Summary: Background and objectives: Due to the development of new anti‐psoriatic drugs in combination with improved structures for implementation throughout Germany, the medical care of psoriasis patients has markedly improved. In this study we investigated the real‐life utilization of the health care system and identified reasons for dissatisfaction in affected individuals. Patients and methods: This non‐interventional cross‐sectional study was conducted as an anonymous online survey from 12/2018 to 01/2019 in Germany. Participants with a self‐reported physician‐confirmed diagnosis of psoriasis and symptoms answered questions about their disease, its influence on daily life and their medical care. Results: 649 participants with a mean age of 42.5 ± 13.7 years and equal gender distribution (male: 50.2 %) were evaluated. 54.1 % received medical treatment at the time of the study, 45.9 % did not. Among the participants with medical care, 59.3 % were only moderately or less satisfied with their treatment. Reasons for dissatisfaction with the medication included lack of efficacy and side effects. Participants without medical treatment specified a physician's lack of time as a main reason for not seeking medical help. Conclusions: Despite the availability of efficient therapeutic options in Germany, many individuals with psoriasis are not satisfied. This under‐treated group was identified as a new target population.